THE RELATIONSHIP BETWEEN CRM, MARKET ORIENTATION, MARKET TURBULENCE AND MARKETING PERFORMANCE: A REVIEW PAPER - Mastura Roni; Siti Hajar Mohamad (International Journal of Accounting, Finance and Business, 2021)
In the commercial world the importance of retaining existing customers andexpanding business is paramount. The costs associated with finding new customers mean thatevery existing customer could be important. However, the customer relationship management(CRM) platform is still arguable as one of the best customer-centric tools on the market. Thisreview paper aims to develop CRM model for Malaysian Food Manufacturing Industry (FMI).This paper builds ongoing research in manufacturing industries and seeks to place CRMpractices in the context of Small and Medium Enterprises (SMEs), which may be particularlysuited to market orientation and market turbulence. The implications of the study contribute tocombination of resources-based view theory, relationship marketing theory and marketorientation theory and provide insights to develop it further. The extensive literature survey amodel is put forth for testing.